No improvement in clinical trial enrollment for adolescents and young adults with cancer at a children's hospital. Issue 12 (16th May 2017) - Jacob, Seethal A.; Shaw, Peter H.
Abstract: Background: We have previously published data from 2001 to 2006 showing that adolescent and young adult (AYA) oncology patients have significantly lower therapeutic clinical trial enrollment rates than younger patients. Our objective was to determine if the enrollment of AYA patients on therapeutic studies at the same institution has improved in recent years with the greater focus on this population locally and nationally. Methods: We retrospectively analyzed cancer registry data at the Children's Hospital of Pittsburgh (CHP) for all new oncologic diagnoses between January 2010 and December 2014. These data included age, gender, diagnosis, race and whether the patient was enrolled on an open treatment study. Univariate analyses were carried out to compare demographic data between AYA patients (aged 15–22) who enrolled on study and those who did not. Results: Eight hundred sixty‐five new oncology patients were seen at CHP during this time, 23% of whom were 15 years or older; 33% of all patients were treated on a clinical trial, including 34% of younger patients and 24% of older patients ( P = 0.0017). The differences between these rates and those from prior years in both age groups (38% and 27%, respectively) were not statistically significant ( P = 0.15, 0.53). The most common reason for the low enrollment rates was again the lack of an open therapeutic trial. Conclusion: Despite initiatives at CHP and on the national level to enroll more AYA patients on clinical trials, our most recent data show no improvement. This is a potentially remediable factor that needs to continue to be prioritized nationally.